Dynamic fracture of the AISI 1045 steel cylinders under internal blast loading. (March 2020) - Ma, Y; He, Y; Wang, CT; He, Y; Guo, Z P; Hu, X B
Abstract: Dynamic fracture failure of the AISI 1045 steel cylinders with variable depth grooves under internal blast loading was investigated. Lateral and longitudinal grooves were curved on the wall of steel cylinders along with radial direction. All grooves have a V-shape with 20° angle. After blast, the morphology of fragments recovered by multi-layer wooden plank showed relative consistency. Microstructure in cross and longitudinal section of the fragments was examined by scanning electron microscope (SEM). The microstructure observation suggested that there were some undeveloped shear bands and the dynamic fracture modes were similar in the all tests but the different fracture mode in two directions. Relevant numerical simulation by LS-DYNA were carried out to analyze the expanding and fracture process of cylinders under internal blast loading. Numerical results have acceptable agreement with experiment results. The mass loss rate of shell after explosion is negatively correlated with the depth of grooves.